Fostering Values in Organizations - Argandoña, Antonio (Journal of business ethics, 2003)
Today, values hold a prominent place both in business ethics and in organization theory. However, there persists considerable confusion about what these values are and what role they play in these theories and, therefore, how they can be developed both within the individual and within the organization. Therefore, this paper seeks to define a conception of values based on a theory of human action that can provide a basis for an organization theory, and to propose a series of ideas about how personal and organizational values can be fostered.